Partisipasi Masyarakat Desa Cihideung Ilir Dalam Perencanaan Pembangunan Desa Sebelum dan Sesudah Wabah Covid-19 - Joko Ahadi Priyanto; Sugeng Heri Suseno (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Covid-19 outbreak was present in the community in 2020 which brought serious attention to the government. The negative impact not only on health problems, but also affects the economy of the country and even the world. This topic will discuss village development planning related to the country's economy before and during the Covid-19 outbreak. The purpose of this study was to analyze community participation in the development planning of Cihideung Ilir Village during the Covid-19 outbreak. The research method used is descriptive qualitative by describing the phenomena and the existing literature. Many professions have been disturbed by the Covid-19 outbreak. The findings of this study suggest that awareness to community participation in promoting village development is the beginning of the community's economic prosperity during the Covid-19 outbreak. The factors that influence participation in the community include gender, age, educational level, employment and income, and the period of residency in an area. Keywords: Covid-19, economy, village development